The role of consumers’ visual attention stimuli in advertising: traditional and neuromarketing research perspectives - Jūratė Banytė; Ieva Pūkienė; Greta Dargytė (Innovative Marketing)
This research aims to reveal the role of consumers’ visual attention stimuli in advertising from traditional and neuromarketing research perspectives. This study examines six stimuli of consumers’ visual attention, which are divided into three groups – complexity of advertising, reflection of reality in advertising, and attributes of advertising content. A conceptual model was developed, encompassing the relationships of the identified stimuli with consumers’ visual attention (via gaze fixation duration and frequency) and with consumers’ attitudes toward advertising. The model was empirically tested using survey questionnaires and an eye-tracking system to analyze a specific food advertising case. A survey involving 403 respondents in Lithuania found that a statistically significant relationship exists between all visual attention stimuli and attitudes toward advertising, except for advertising authenticity (p-value>0.05). However, the results of the linear regression confirm only instrumental attributes in advertising content (R2=0.294) and higher design complexity (R2=0.230) positively influence on consumer attitudes toward advertising. In the neuromarketing study with 26 participants, a significant relationship was revealed between both dependent variables (the duration and frequency of participants gaze) and visual attention stimuli in food advertising. ANOVA analysis results show longer gaze fixation duration for simple, clear designs, manipulative advertising, symbolic content attributes; more frequent gaze fixation for advertising reflecting high functional and design complexity, authenticity, and instrumental content attributes. However, no relationship was found between gaze variables and consumer attitudes, except for authentic advertising, where higher greater gaze frequency was linked to a more positive attitude.